Le préarchivage : organisation et techniques (22e Congrès des Archives de France) (Gazette des archives, 1978)
«Préarchivage » : organisation and technique. Folio wing the theme of the 1977 Congres s, the 1978 Congres s of French Archivists discussed the question of «préarchivage » procedures, which ought to be systematised by specific régulations ; it also discussed the possible application of microfilm techniques to «préarchivage ». The discussion proved the importance of these problems.

La gestion des archives audiovisuelles à l'Institut national de l'audiovisuel - Dumont, J. (Documentaliste, 1978)